Pemodelan Interaksi Medan Listrik Dinamis dan Gelombang Elektromagnetik - Monang Marpaung; Gideon Fercy Silitonga; Wandani Putri Siregar; Arwadi Sinuraya; Desman Jonto Sinaga (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research stems from the need to understand the complex relationship between time-varying electric fields and electromagnetic waves, which often presents difficulties in simulating their propagation in various media. The primary focus is to develop a numerical model capable of predicting the dynamics of this interaction, thus enabling its use in antenna development and radiation evaluation. The applied method includes a Finite-Difference Time-Domain approach, which solves the fundamental equations stepwise in both the time and space domains. The results show that the model is capable of reproducing transverse propagation patterns with a high degree of accuracy and detecting strong mutual induction effects at high frequencies. These findings provide a foundation for improving the performance of electromagnetic devices, minimizing potential interference, and opening up new innovations in the telecommunications sector.